Visual and Verbal Rhetoric in Islamicate Manuscripts: A Semiotic and Multimodal Perspective - Khadjimetov, Bekhzod B.; Madraimov, Abdumadjid; Djumaniyazov, Shixnazar; Kalbaeva, Maftuna Kh.; Rakhmatullaeva, Asalkhon G.; Askarova, Zilola A. (Jurnal Arbitrer, 2025)
This article presents a series of reflections on the visual and verbal rhetoric of Baburite art, with a particular emphasis on the interplay between visual and textual elements in Islamicate manuscripts. It particularly critiques the semiotic and multimodal methods employed to decipher the artistic customs of the period, specifically the reign of Zahiruddin Muhammad Babur and his descendants. The work offers a psychological analysis of miniatures, calligraphy, and inscriptions as powerful rhetorical tools to disseminate the imperial message, establishes cultural and national identity through their connection with various religions, and fosters political legitimacy. The paper itself also highlights Babur’s impact on the evolution of Indian painting, particularly his role in importing Persian and Central Asian art practices that would meld with regional styles in India to form a distinct Mughal visual culture. As a result of cultural hybridity, Babur’s artistic contribution informed the art direction of Mughal viceroys for their visual and literary narratives. This article highlights several key themes, including Persian, Central Asian, and Indian influences, and focuses on the significance of considering Baburite art as a vehicle for artistic representation and propaganda. The paper advocates for a more unified approach to considering Baburite art as a simultaneous cultural expression and imperial communication.